Test Instrument Validation of Two Dimensional Geometry Using Rasch Model - Eyus Sudihartinih; Sufyani Prabawanto (MEJ (Mathematics Education Journal), 2020)
The purpose of this study is to describe the results of the analysis of the quality of the mathematical students' initial ability in the field of geometry concepts through the Rasch model. This research is descriptive qualitative research at a university in Indonesia. The participants of this study were 44 students who studied analytic geometry (30 women and 14 men). This research instrument is a matter of description of the concept of geometry as many as four questions. Based on the results of the study note that all items meet the standard criteria as measurement so that the questions can be used as instruments in further research.